Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Second law:

The rate of change of momentum is directly proportional to the applied force and takes place in the direction that the force acts.

F α Δp / Δt = k Δp/Δt = k Δ(m v) Δt = k m Δv/Δt = k m a

as Δv/Δt = dv/dt = acceleration

We choose k = 1 So F = ma

Let us say body1 exerts a force F1 on body 2 and the body 2 exerts a force F2 on body1. These two bodies are in isolation. Let their masses be m1 and m2 respectively.

From the second law and first law, when there is no external force acting on them (or the system of body1 and body2), the acceleration of the system is zero. So the total momentum of the system remains constant.

p1 = m1 u1 at time t1 and m1 v1 at t = t2. p2 = m2 u2 at t = t1 and p2 = m2 v2 at t = t2.

p1 + p2 = constant

m1 v1 + m2 v2 = m u1 + m2 u2

m1 (v1 - u1) = - m2 (v2 - u2)

m1 (v1 - u1) / (t2 - t1) = - m2 (v2 - u2) / (t2 - t1)

m1 Δv1 / Δt = - m2 Δv2 / Δt

m1 a1 = - m2 a2

This is the third law.

The rate of change of momentum is directly proportional to the applied force and takes place in the direction that the force acts.

F α Δp / Δt = k Δp/Δt = k Δ(m v) Δt = k m Δv/Δt = k m a

as Δv/Δt = dv/dt = acceleration

We choose k = 1 So F = ma

Let us say body1 exerts a force F1 on body 2 and the body 2 exerts a force F2 on body1. These two bodies are in isolation. Let their masses be m1 and m2 respectively.

From the second law and first law, when there is no external force acting on them (or the system of body1 and body2), the acceleration of the system is zero. So the total momentum of the system remains constant.

p1 = m1 u1 at time t1 and m1 v1 at t = t2. p2 = m2 u2 at t = t1 and p2 = m2 v2 at t = t2.

p1 + p2 = constant

m1 v1 + m2 v2 = m u1 + m2 u2

m1 (v1 - u1) = - m2 (v2 - u2)

m1 (v1 - u1) / (t2 - t1) = - m2 (v2 - u2) / (t2 - t1)

m1 Δv1 / Δt = - m2 Δv2 / Δt

m1 a1 = - m2 a2

**F2 = - F1**This is the third law.